2016
DOI: 10.1371/journal.pone.0146345
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Aphis gossypii Glover (Hemiptera: Aphididae) Biotypes from Different Host Plants in North China

Abstract: BackgroundThe cotton-melon aphid, Aphis gossypii Glover (Hemiptera: Aphididae), is a polyphagous species with a worldwide distribution and a variety of biotypes. North China is a traditional agricultural area with abundant winter and summer hosts of A. gossypii. While the life cycles of A. gossypii on different plants have been well studied, those of the biotypes of North China are still unclear.ResultsHost transfer experiments showed that A. gossypii from North China has two host-specialized biotypes: cotton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 34 publications
1
52
0
1
Order By: Relevance
“…We did not measure the nearest distance of primary host plants from where aphids migrated. It has been reported that many plant species serve as primary hosts in North China, such as Hibiscus syriacus (hibiscus), Punica granatum (pomegranate), and Zanthoxylum simulans (Chinese prickly ash) (Wang et al., ). Moreover, these primary hosts are seldom planted in large areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not measure the nearest distance of primary host plants from where aphids migrated. It has been reported that many plant species serve as primary hosts in North China, such as Hibiscus syriacus (hibiscus), Punica granatum (pomegranate), and Zanthoxylum simulans (Chinese prickly ash) (Wang et al., ). Moreover, these primary hosts are seldom planted in large areas.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the populations with an incomplete life cycle (or anholocycle), holocycle populations sexually reproduce. Evidence for high genetic diversity associated with sexual reproduction of A. gossypii has been found in China (Wang et al, 2016), France (Thomas, Boissot, & Vanlerberghe-Masutti, 2012), and Iran (Razmjou, Vorburger, Moharramipour, Mirhoseini, & Fathipour, 2010). In addition, other factors such as insecticide selection pressure and competition can also affect genetic diversity (Brévault, Carletto, Linderme, & Vanlerberghe-Masutti, 2008;Brévault, Carletto, Tribot, & Vanlerberghe-Masutti, 2011;Carletto, Martin, Vanlerberghe-Masutti, & Brévault, 2010;Fuller et al, 1999).…”
mentioning
confidence: 99%
“…This is possibly due to the fact that wheat is planted in fall/winter and harvested in summer in China (Ma et al 2006). Moreover, the reproduction mode of A. gossypii is sexual in fall/winter when their major hosts are Hibiscus syriacus (hibiscus), Punica granatum (pomegranate), and Zanthoxylum simulans (Chinese prickly ash) (Liu et al 2014;Wang et al 2016). Thus, we speculate that wheat is just a short-term host of asexual females early in summer when wheat is in a mature period and lacks adequate nutrition for aphids.…”
Section: Discussionmentioning
confidence: 99%
“…In many areas of northern China, cotton-wheat intercropping is an important cultural model beside monoculture cotton fields (Wang et al 2016). Winter wheat is sown from early-to mid-October with a designated row A l x f (x, 5) m x l x m x Survival rate (%) Survival rate (%) Fig.…”
Section: Discussionmentioning
confidence: 99%
“…glycines uses the soybean plant as a summer host and a few species in the genus Rhamnus as the overwintering host, while Ap. gossypii utilizes over 900 species of plants (Blackman and Eastop, 1984;Carletto et al, 2009;Wang et al, 2016). Despite its widespread distribution and highly polyphagous nature the cotton aphid has the smallest genome of the currently available aphid genome assemblies and was found to have the lowest number of private genes (Quan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%